Βιβλιοκρισία:G. THEOTOKIS, Byzantine Military Tactics in Syria and Mesopotamia in the 10th Century. A Comparative Study, Edinburgh 2018 - KARATOLIOS, Konstantinos (Byzantina Symmeikta, 2019)
Βιβλιοκρισία G. Theotokis, Byzantine Military Tactics in Syria and Mesopotamia in the 10th Century. A Comparative Study, Edinburgh 2018, pp. 348. ISBN 978-1-47-443103-3.